Expansion of FasL-Expressing CD5+ B Cells in Type 1 Diabetes Patients - Saxena, Ankit; Yagita, Hideo; Donner, Thomas W.; Hamad, Abdel Rahim A. (Frontiers in Immunology, 2017)
Fas ligand drives insulitis in the non-obese diabetic (NOD) mouse model of type 1 diabetes (T1D) and negatively regulates IL-10-producing (IL-10pos) CD5+ B cells in pancreata. Relevance of these phenomena to the human disease is poorly understood. Here, using splenocytes from T1D, autoantibody (Ab+) and non-diabetic (ND) human subjects, we show that a subpopulation of CD5+ B cells that is characterized by expression of FasL (FasLhiCD5) was significantly elevated in T1D subjects, many of whom had significantly reduced frequency of IL-10posCD5 B cells compared to Ab+ subjects. The majority of FasLhiCD5 B cells did not produce cytokines and were more highly resistant to activation-induced cell death (AICD) than their IL-10posCD5 counterparts. These results associate expansion of FasL-expressing CD5 B cells with T1D and lay the groundwork for future mechanistic studies to understand specific role in disease pathogenesis.